Time assessment of tectonic and climatic forcing on the formation of Khari bedrock gorge, Kachchh, western India: A mathematical approach. (20th February 2021) - Thakkar, M.G.; Kothyari, Girish Ch; Jani, Chirag; Chauhan, Gaurav; Lakhote, Abhishek; Taloor, Ajay Kumar
Abstract: Formation of large-scale deformations in the upper part of the crust during Quaternary resulted in the opening of cracks on the rising/bulging landscape of the E-W trending Kachchh basin. The present study pertains to the development of a deep Khari bedrock gorge (an open crack) in the mainland region of Central Kachchh, western India. The length of the crack, the narrow bedrock gorge is 220 m and the maximum depth is 27.3 m. The estimated results show the maximum dip dimension 49.9 m and a minimum 3.1 m. The study shows that there is a regular and direct connection between the size (length) of crack openings and the rate of displacement. However, the controlling dimension of displacement and widening of the fracture depends on volumetric fluid flow, overpressure of fluid, the ratio of length-displacement/width, and an elastic limit of sandstone, the host rock. The controlling dimension of a crack is geometrically denoted by the strike and dip of a fracture. The volume of water flow, the volumetric rate on the horizontal bedrock surface, and the subsequent crack opening is directed by the fracture aperture. The opening of a crack within the contact of two surfaces may have a variable aperture corresponding to the rate of volumetric fluid flow over the crack. The statistical parameter shows that the Young's modulus of sandstone is 6 MPa and the Poisson's ratio is 0.2 and the Tensile strength 14 MPa of the fault zone. Our estimates show that the initial opening displacement of Khari gorge is 0.6–0.8 mm with an initial volumetric rate of fluid is 22 Qc indicates enhanced discharge. Further, it is noticed that the fluid passing through the crack caused its widening by 0.2 mm with a gradual decrease of volumetric fluid rate 3Qc through the cracks during the decline condition of fluid discharge. The empirical relation of fracture direction with time factor suggests that the initial stage of gorge formation took place around 125 ka (Late Pleistocene) ago during the effective climatic condition and continuous modification for shaping the gorge took place until around 8 ka (Holocene). After that, the modification through climate is completely ceased.